2004
DOI: 10.1007/bf03218403
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of silica nanoparticle reinforced poly(ethylene 2, 6-naphthalate)

Abstract: We added surface-modified silica nanoparticles to poly(ethylene 2,6-naphthalate) (PEN) to investigate their effect on the mechanical properties on the PEN nanocomposite material. The torque and total torque values of the composites decreased in the silica nanoparticle composites. The tensile modulus of the composites reinforced with unmodified silica nanoparticles increased upon increasing the silica content, while the tensile strength and elongation decreased accordingly. In contrast, stearic acid-modified, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Ahn et.al. reported that the tensile modulus of composites reinforced with unmodified silica nanoparticles improved upon increasing the silica content, however, the elongation to failure decreased [9]. A research group at Toyota developed an economic industrial process for the manufacture of polymer/clay nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Ahn et.al. reported that the tensile modulus of composites reinforced with unmodified silica nanoparticles improved upon increasing the silica content, however, the elongation to failure decreased [9]. A research group at Toyota developed an economic industrial process for the manufacture of polymer/clay nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an increase in elongation at break and tensile strength when the nano‐size silica was loaded to the polymer matrix. The elongation at break and tensile strength showed a tendency to increase until the filler content reached a critical loading level . During the deformation of the plastic, small spherulites with many grain boundaries can inhibit cracks from growth by restricting the dislocation motion.…”
Section: Resultsmentioning
confidence: 99%
“…Fumed silica is made from pyrolysis of SiCl 4 and has a branched‐chain‐like aggregation structure. Studies have shown that fumed silica acts as a nucleating agent, and increases thermal stability, tensile strength and elongation at break …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the E ′ composite values of the AP/EP/SiO 2 composites scarcely increased with increasing SiO 2 content. It is worth noting that the E ′ composite values of the AP/EP/SiO 2 composites hardly changed, regardless of the content of rigid filler, although the modulus of the composites increased in an exponential manner with the content of rigid filler with far higher moduli than the polymeric material . Nielsen proposed the following equation [eq. ]…”
Section: Resultsmentioning
confidence: 99%
“…The modulus of two‐component polymer/filler composites depends on those of each component and the ϕ value of filler. The theoretical modulus of the polymer/filler composites was proposed by Neilsen and Halpin and Kardos In general, it is well‐known that the dynamics of the polymer component in a simple composite is not affected by the filler component . Therefore, many researchers have focused on the improvement of the affinity between the polymer chain and the filler.…”
Section: Introductionmentioning
confidence: 99%